PERDARAHAN ILIOPSOAS PADA PASIEN COVID-19 DALAM TERAPI ANTIKOAGULAN - Priyana, Andria (Fakultas Kedokteran Universitas Tarumanagara, 2021)
Background: Giving anticoagulants to Covid-19 patients is included in one of the standard protocols for Covid-19 therapy. The focus on anticoagulation to prevent thrombotic events often creates a “double-edged sword” with the risk of bleeding, which is also potentially fatal. We present a rare but fatal case of iliopsoas hemorrhage.Case: A Covid-19 patient, 70 years old male, received anticoagulant therapy with unfractionated heparin instead of enoxaparine (LMWH) due to high D-dimer. As the D-dimer value improves, massive and continuous left iliopsoas hemorrhage appears which causes hemodynamic disturbances. Fluid resuscitation, vasopressors, and transfusions were administered following a CT scan of the abdomen. Follow-up CT angiography could not locate the source of the bleeding. Surgery or percutaneous intervention cannot be performed. The patient eventually died.Conclusion: The incidence of bleeding on anticoagulant therapy is low, especially iliopsoas bleeding. Given the massive anticoagulant therapy in almost all Covid-19 patients, as well as the pathogenesis of Covid-19 that interferes with vascular conditions and the coagulation system, the incidence of bleeding risk may increase. This needs to be a concern and anticipation of comprehensive management.